AGE-RELATED CHANGES IN THE RESPIRATORY SYSTEM AND THEIR PHYSIOLOGICAL SIGNIFICANCE - Irgasheva Dildora Ganiyevna (International Journal of Literature and Language Studies, 2026)
The respiratory system undergoes significant structural and functional changes throughout the aging process. These changes affect lung elasticity, respiratory muscle strength, gas exchange efficiency, and overall pulmonary function. Understanding age-related alterations in the respiratory system is essential for maintaining respiratory health and preventing chronic pulmonary diseases. This article examines the physiological changes that occur in the respiratory system with aging and discusses their impact on respiratory function and overall health. The findings indicate that age-related respiratory changes can reduce functional reserve capacity and increase susceptibility to respiratory disorders.